'Distant socializing, ' not 'social distancing' as a public health strategy for COVID-19. (18th August 2021) - Pandi-Perumal, Seithikurippu R.; Vaccarino, Sophie R.; Chattu, Vijay Kumar; Zaki, Nevin F.W.; BaHammam, Ahmed S.; Manzar, Dilshad; Maestroni, G J M; Suchecki, Deborah; Moscovitch, Adam; Zizi, Ferdinand; Jean-Louis, Girardin; Narasimhan, Meera; et al.
ABSTRACT: Social distancing, also referred to as physical distancing, means creating a safe distance of at least two meters (six feet) between yourself and others. This is a term popularized during the COVID-19 pandemic, as it is one of the most important measures to prevent the spread of this virus. However, the term 'social distancing' can be misleading, as it may imply that individuals should stop socializing. However, socializing in a safe context (i.e. over the phone, video-chat, etc.) is especially important during this time of crisis. Therefore, in this narrative review, we suggest the term 'distant socializing' as more apt expression, to promote physical distancing measures while also highlighting the importance of maintaining social bonds. Further, articles discussing the practice, implementation, measurement, and mental health effects of physical distancing are reviewed. Physical distancing is associated with psychiatric symptoms (such as anxiety and depression), suicidal ideation, and domestic violence. Further, unemployment and job insecurity have significantly increased during COVID-19, which may exacerbate these negative mental health effects. Governments, medical institutions, and public health bodies should therefore consider increasing mental health resources both during and after the pandemic, with a specific focus on frontline workers, COVID-19 survivors, and marginalized communities.